Regeneração in vitro e transformação genética de cultivares de mandioca (Manihot esculenta Crantz) do Nordeste brasileiro - Machado, Terezinha Feitosa (2004)
Several regenerations systems, such as somatic embryogenesis and shoot organogenesis, and the Agrobacterium tumefaciens genetic transformation system were evaluated objecting the establishment of reliable protocols for the genetic improvement of cassava cultivars from the northeastern Brazil. Direct somatic embryogenesis were aUained from shoot apexes of numerous cassava genotypes, when explants were cultivated in MS medium with 1-15 mgll picloram, supplemented with sucrose, copper sulfate and Agar. Different cultivars exhibited noticeable diverse embryogenic potentials. Cyclic somatic embryogenesis was induced by subculturing in solid induction medium. Plants were regenerated by shoot induction, in explants resultant from cyclic somatic embryos green cotyledons. After transfer to elongation medium, regenerated shoots rooted in hormone free medium. A DNA transformation protocol was established for somatic embryos green cotyledons. The plasmids employed for genetic transformation harbored genes coding for neomicine phosphotransferase (nptll), hygromicine phosphotransferase (hpt) and for J3- glucuronidase (uidA). In the majority of the explants, histochemical evidences revealed the GUS presence, confirming the transient gene expression.